2009
DOI: 10.1016/j.jtcvs.2008.11.017
|View full text |Cite
|
Sign up to set email alerts
|

A new strategy for prevention of anastomotic stricture using tacrolimus-eluting biodegradable nanofiber

Abstract: Tacrolimus-eluting biodegradable nanofiber reduced neointimal hyperplasia and preserved endothelialization. This device may be useful in the prevention of anastomotic stricture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…There are several reports urging the establishment of DDS using electrospinning biodegradable polymers [55e57]. We have been developing DDS using electrospinning biodegradable polymers for cardiovascular medicine [58,59]. DDS of the DCRBF is quite simple: DOXY is released with hydrolysis of the PLA, and the DCRBF appears like a cotton wool.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports urging the establishment of DDS using electrospinning biodegradable polymers [55e57]. We have been developing DDS using electrospinning biodegradable polymers for cardiovascular medicine [58,59]. DDS of the DCRBF is quite simple: DOXY is released with hydrolysis of the PLA, and the DCRBF appears like a cotton wool.…”
Section: Discussionmentioning
confidence: 99%
“…12 In brief, simvastatin (Toronto Research Chemicals, Inc., North York, ON, Canada) (MW = 418.57) was mixed with biodegradable polymer to fabricate SRBFS, and not mixed to fabricate BFS. Poly(L-lactide-co-glycolide) (IV = 1.15 dL/g), which consists of 50% of each polymer, was prepared for the biodegradable polymer.…”
Section: Isolation and Expansion Of Bmscsmentioning
confidence: 99%
“…2 Meanwhile, our previous studies reported a sustained drug delivery system (DDS) using electrospinning biodegradable fiber with various types of drugs. 12,13,31 Sustained drug release can be adjusted by modification in the polymer degradation and can contribute to minimizing systemic influences and adverse side effects, while maximizing the local effects. Furthermore, the electrospinning process provides engineering scaffolds with nano-to microscale topography and high porosity similar to the natural extracellular matrix (ECM).…”
Section: Introductionmentioning
confidence: 99%
“…We have been developing a drug-containing biodegradable nano-scaled fibre, using an electrospinning technique to achieve a local and sustained release of drugs [9][10][11]. In this study, we applied this technology for the controlled release of vasodilators to prevent arterial spasm.…”
Section: Fabrication Of Drug-releasing Biodegradable Nano-scaled Fibrementioning
confidence: 99%